Towards a Dual Lateral Flow Nanobiosensor for Simultaneous Detection of Virus Genotype-Specific PCR Products - Dimitra K. Toubanaki; Evdokia Karagouni (Journal of Analytical Methods in Chemistry)
Nervous necrosis virus (nodavirus) has been responsible for mass mortalities in aquaculture industry worldwide, with great economic and environmental impact. A rapid low-cost test to identify nodavirus genotype could have important benefits for vaccine and diagnostic applications in small- and medium-scale laboratories in both academia and fish farming industry. A dual lateral flow biosensor for simultaneous detection of the most prevalent nodavirus genotypes (RGNNV and SJNNV) was developed and optimized. The dual biosensor consisted of two antibody-based test zones, indicative of each genotype, and a control zone. The positive signals were visualized by gold nanoparticles functionalized with anti-biotin antibody, and the detection was completed within 20 min. Optimization studies included antibody type and amount determination for test zone construction, gold nanoparticle conjugate type selection for high signal generation, and detection assay parameter determination. Following optimization, the biosensor was evaluated with healthy and RGNNV-nodavirus-infected fish samples. The proposed assay’s cost was estimated to be less than 3 €, including the required reagents and biosensor. This work presents important steps towards making a dual lateral flow biosensor for nodavirus genotyping; further evaluation with clinical samples is needed before the test is appropriate for diagnostic kit development.